Investigating tourist's behavioral intentions using stimulus-organism response theory - Ku, Wen Xin; Lim, Siew Sin; Look, Kah Sin; Tan, Woei Hern (2019)
Heritage tourism becoming popular in the recent years. The number of tourists to the cultural heritage sites having a drastic increase. This has brought many positive impacts to tourism industry. Nevertheless, the motives of tourists visiting the cultural heritage sites were varied. Hence, this study investigates the stimuli lure the tourists to visit such sites. Past studies using Stimulus-Organism-Response Model is limited in tourism context. To address the gap in the literature, the study guided by Stimulus-Organism-Response (S-O-R) model to discover tourists’ attitude, interpretation and experience as “Stimulus”, emotions as “Organism” and behavioural intentions as “Response”. The objective of this study is to examine the level of tourists’ attitude towards World Heritage Sites and to investigate the relationship among the proposed constructs in the S-O-R model. The data of this research was collected from 250 domestic and foreign tourists visiting Georgetown, Penang which is one of the World Heritage sites recognized by United Nations Educational, Scientific and Cultural Organization (UNESCO). The result revealed nearly half of the respondents have moderate and positive attitude towards UNESCO World Heritage Brand. In addition, the relationship between tourists’ attitude, interpretation and experience and emotions are theorized as positive and significant. The result demonstrated experience has the highest impact on tourists’ emotions compared to another two stimuli. The final result has proven that stimulus variables had significantly associated with emotional responses and led to favourable behavioural intentions among tourists. Applying the S-O-R model was able to enrich the application of the model in diverse settings.